Characteristics of Drug Sensitive Pulmonary Tuberculosis Patients in Primary Health Center Laubaleng During Covid-19 - Lily; Fujiati, Isti Ilmiati (TALENTA Publisher, Universitas Sumatera Utara, 2024)
Background: Primary Health Center Laubaleng (PHCLB) first used the System Information Tuberculosis (SITB) at the start of the COVID-19 pandemic. SITB is more effective and efficient than manual, contains TB patient data, and is easy to view again. This research aims to describe the characteristics of Drug Sensitive Pulmonary TB (DSPTB) patients at the PHCLB during COVID-19 from SITB which is useful for detecting TB risk group cases. Method: The research type was descriptive quantitative with a cross-sectional approach by comparing each age group, productivity, and gender. All DSPTB patients were recorded and reported in the SITB PHCLB database during the COVID-19 pandemic from January to December 2020, 2021, and 2022. SITB database access permitted by PHCLB, Jl. Renun, No. 597, Laubaleng District, Karo Regency, North Sumatra Province, Indonesia Results: The largest percentage of DSPTB patients were aged 45-54 years in year 2022 (41.4%). The productive age category (15-64 years) dominated not (â‰¥65 years) and not yet productive (0-14 years) in 2020, 2021, and 2022, respectively 90.9%, 85.4%, and 86.2%. The total number of DSPTB decreased in 2020, 2021, and 2022, respectively 55, 48, and 29 people. Conclusion: Characteristics of DSPTB from SITB PHCLB during the Covid-19 pandemic, were mostly in the adult age category 45-54 years, productive (15-64 years), male and total number of patients decreased by 7 and 19 people respectively.